2018
DOI: 10.1080/21645515.2018.1489190
|View full text |Cite
|
Sign up to set email alerts
|

Facilitators and barriers for use of rotavirus vaccine amongst various stakeholders and its implications for Indian context – A systematic review

Abstract: Improved awareness regarding the rotavirus vaccination amongst public and scientific community and strengthening of public health system for better and timely immunisation coverage are important factors to maximize uptake of rotavirus vaccine in India.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 39 publications
0
13
0
1
Order By: Relevance
“…We thematically analyzed and categorized text fragments from the 37 reviews that discussed methodological and conceptual aspects of their barriers and facilitators approach. This subsample was generally of higher methodological quality compared to the full sample of reviews and only included one review with a low transparency rating 31 . The full transparency ratings of the subsample can be found in Data S6.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We thematically analyzed and categorized text fragments from the 37 reviews that discussed methodological and conceptual aspects of their barriers and facilitators approach. This subsample was generally of higher methodological quality compared to the full sample of reviews and only included one review with a low transparency rating 31 . The full transparency ratings of the subsample can be found in Data S6.…”
Section: Resultsmentioning
confidence: 99%
“…This subsample was generally of higher methodological quality compared to the full sample of reviews and only included one review with a low transparency rating. 31 The full transparency ratings of the subsample can be found in Data S6. Two overall categories of themes emerged in the analysis: (a) Methodological and practical issues in conducting barriers and facilitators reviews, and (b) definitional and conceptual issues related to barriers and facilitators.…”
Section: Reviewer Reflections On Analyzing Barriers and Facilitatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…VaduHDSS has contributed to national programs on immunization, tubectomy, vasectomy, tuberculosis control, childhood disability identification program and development of community health volunteer schemes. Examples of some study findings which have made their way to implementation by the public health system include Sprinkles micronutrient powder [13,14] and iron fortified wheat flour [15] as well as vaccine studies on Rota virus vaccine [16-21]. Studies conducted in VaduHDSS, in addition to providing evidence to government, have created significant scientific literature as outcome of its studies [22].…”
Section: How Has Vaduhdss Data Been Usedmentioning
confidence: 99%
“…Many of the included reviews reported the inability to conduct a quantitative meta-analysis as a limitation to the synthesis (e.g. [34,51,61,[70][71][72][73]), despite the fact that they posed questions that were qualitative in nature. Notably, most included research by the reviews was qualitative and a third of the SRs (31%) only sought qualitative studies; however, many review papers adopted a quantitatively oriented language suggesting that the most frequently reported factors were, in fact, the most important.…”
Section: Synthesising 'Barriers' and 'Facilitators'mentioning
confidence: 99%